The Cambridge history of religions in Latin America - Garrard, Virginia; Freston, Paul; Dove, Stephen C. (Cambridge University Press, 2016)
"The Cambridge History of Religions in Latin America covers religious history in Latin America from pre-Conquest times until the present. This timely publication is important, firstly, because of the historical and contemporary centrality of religion in the life of Latin America, a region which has been growing in global importance; secondly, for the rapid process of religious change which the region is undergoing; and thirdly, for the region's religious distinctiveness in global comparative terms, which contributes to its importance for debates over religion, globalization, and modernity, not least because Latin America now has more Catholics and more Pentecostals than any other region of the world. Unlike most works on religion in the region, and in recognition of recent strides in scholarship, this volume addresses the breadth of Latin American religion, including religions of the African diaspora, indigenous spiritual expressions, new religious movements, alternative spiritualities, and secularizing tendencies"--